The Importance of Daily Activity for Reducing Fibromyalgia Symptoms: A Retrospective “Real World” Data Comparison of two Multimodal Treatment Programs - Sybille KRAMER,; Lana DEUSCHLE,; Niko KOHLS,; Martin OFFENBÄCHER,; Andreas WINKELMANN, (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate the effectiveness of two multidisciplinary fibromyalgia programs with different intensities. Materials and methods: In this retrospective real-world comparison of patient data, pre- and post-program datasets of Short Form 36 (SF36) and Fibromyalgia Impact Questionnaire (FIQ) were obtained from a total of 210 female patients in two fibromyalgia multidisciplinary day hospital programs including one intensive program with daily treatments summing up to 20 treatment days during four weeks (P20, n=70) versus a less intensive program with 12 treatment days during four weeks (P12, n=140). Results: Multiple subscales of SF36 and FIQ were improved in the pre-post comparison in both groups. In the comparison between the two groups, a statistically significantly higher improvement was found in the P20 group compared to the P12 group for the FIQ subscales of stiffness (p=0.001) and the number of days during which the patient felt “good” (p=0.007). Conclusion: An intensive program of daily treatments and activity seems to be more effective in reducing fibromyalgia-associated stiffness and improving the number of days during which patients feel good than a less intensive program.